Gold Extraction Process with Base-Case Sample and Aachen Assisted Leaching (AAL) using Running Aachen at The Mineral And Coal Testing Center Tekmira, Bandung Jawa Barat - Brilian, Oktavio Yorris; Wahyuningsih, Tri (Journal of Metallurgical Engineering and Processing Technology, 2024)
The Center for Mineral and Coal Testing is an institution that works in the field of research services on mining and mineral processing. In the mineral processing research currently being carried out there is a research project related to increasing the efficiency of the leaching process using the Aachen Reactor. The samples used in this research were refractory gold samples. The problem of reducing the effectiveness of gold leaching is that there are minerals that are still included in the associated minerals, therefore a pre-treatment process is needed to remove these associated minerals. The Aachen reactor will help increase the efficiency of the leaching process by increasing Dissolve Oxygen levels to 30 ppm. In this study, two samples were used for comparison, namely the Pre-Ox sample and the Aachen Assisted Leaching (AAL) sample.